D8.14 Report on the Industry Liaison Office activities - Papoutsa, Christiana; Hadjimitsis, Diofantos G.; Eliades, Marinos; Theocharidis, Christos; Leventis, Georgios; Pekri, Marina; Themistocleous, Kyriacos (My University, 2022)
This deliverable reports the activities that were done with stakeholders to co-design, co-develop, commercialise, and promote EO-based products & services and applications that facilitate the efficient use of EO data for different economic sectors (e.g., tourism, energy, agriculture) up to date. This deliverable also describes the need for the Eratosthenes Centre of Excellence (ECoE) to set up an industry liaison office (ILO), as the first point of contact for industrial actors in Cyprus, EMMENA and in Europe, for linking and documenting the ECoE with industrial needs, cultivating mutually beneficial relationships with the industry, preparing the ground for cooperation, handling MoUs and contracts and involving the appropriate ECoE and Digital Innovation Hub (DIH) staff towards ECoE income diversification and sustainability.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation; Digital Innovation Hub